Refurbishing the historic Old Tweed Bridge, Scotland – the challenges and innovations. Issue 4 (13th July 2019) - Grubb, Andrew; O'Connor, Kieran; McDonald, Hazel
Abstract : The historic Old Tweed Bridge is a three-span listed masonry arch crossing the River Tweed. Structural integrity concerns resulted in the bridge being temporarily closed to the public and propped. This paper discusses the challenges associated with the construction works necessary to refurbish the bridge permanently. The works involved installing a temporary propping and encapsulation structure, excavating the bridge infill, taking down and rebuilding the walls, casting a concrete saddle above the arches, waterproofing and resurfacing. Other innovative works involved closing the gap between the voussoirs and arch barrel using a bespoke arch pulling system and repairing voussoir stones in situ with a lime-based material. There were significant environmental challenges on the project as the bridge is located in an ecologically sensitive area. The River Tweed is one of the UK's great salmon rivers, which restricted working in the river and required strict pollution controls. Alternative roosts for bats were provided and netting was required around the bridge as part of an advanced works contract to mitigate the risk of birds nesting in the bridge.